2019
DOI: 10.1111/cas.13919
|View full text |Cite
|
Sign up to set email alerts
|

Significant differences in T cell receptor repertoires in lung adenocarcinomas with and without epidermal growth factor receptor mutations

Abstract: Recent clinical trials of non‐small cell lung cancer with immune checkpoint inhibitors revealed that patients with epidermal growth factor receptor (EGFR) mutations had more unfavorable outcomes compared with those with wild‐type EGFR. However, the underlying mechanism for the link between EGFR mutations and immune resistance remains unclear. We performed T cell receptor (TCR) repertoire analysis of resected lung adenocarcinoma tissues with and without EGFR mutations to investigate the characteristics of TCR r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
3
11
1
Order By: Relevance
“…Despite the heterogeneity of the study population, our findings are consistent with previous reports that patients with PD-L1 ≥50% fare better with ICIs and patients who had EGFR mutations had worse OS than patients who were EGFR negative treated with ICIs [10]. The underline mechanism of lack of benefits in EGFR mutated tumors remains unclear and a recent study of T cell receptor repertoire analysis showed that EGFR-mutated tumors had lower clonal T cell expansion compared with EGFR non-mutated tumors [31]. Our real-world experience with patient populations in different settings from clinical trials validated the role of PD-L1 level ≥50% and EGFR mutations in ICIs.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the heterogeneity of the study population, our findings are consistent with previous reports that patients with PD-L1 ≥50% fare better with ICIs and patients who had EGFR mutations had worse OS than patients who were EGFR negative treated with ICIs [10]. The underline mechanism of lack of benefits in EGFR mutated tumors remains unclear and a recent study of T cell receptor repertoire analysis showed that EGFR-mutated tumors had lower clonal T cell expansion compared with EGFR non-mutated tumors [31]. Our real-world experience with patient populations in different settings from clinical trials validated the role of PD-L1 level ≥50% and EGFR mutations in ICIs.…”
Section: Discussionsupporting
confidence: 90%
“… 37 Through whole-exome sequencing of these paired samples, top frequently somatic-mutated genes such as EGFR , TP53 , and TTN , etc., whose mutations were well-known in lung cancer, were further studied with TCR repertoires. Although it has been previously reported that EGFR mutant tumors had a higher TCRβ diversity index than WT tumors, 38 difference of TCR repertoires in tumors with and without EGFR mutation was not observed in our study ( Figures 4 A–4D). Instead, TTN gene somatic mutation was shown to affect the profiling of intratumoral TCR repertoires ( Figures 4 I–4L), this results could be one of reasons of the correlation of TTN mutations with favorable prognosis in lung squamous cell carcinoma.…”
Section: Discussioncontrasting
confidence: 85%
“…96,97 A higher TCR diversity index in EGFR-mutated than EGFR wild-type tumors might suggest a higher Tcell clonal expansion in EGFR wild-type tumors. 98 This could indirectly point to a possible reason for the unfavorable response of EGFR-mutated NSCLC to ICI. However, there are currently no published data on the predictive role of TCR clonality and diversity and their correlation with other biomarkers, including PD-L1 and TMB.…”
Section: Tmb Assay Cross Comparison and Harmonization Effortsmentioning
confidence: 99%